Peningkatan Pemahaman Konsep Menguraikan dan Menyusun Bilangan dengan Metode Matematika Realistik dalam Pengembangan Kurmer di Kelas I SDN Bendogerit 2 Kota Blitar - Tanjung Anugrah Widhi (LP. Ma'arif Janggan Magetan, 2022)
athematics education in the independent learning curriculum provides opportunities for students to learn freely and comfortably, relax and be happy without stress, study quietly without any pressure from the school. Learning mathematics in elementary school is the beginning of a child's beginning to explore his ability to understand concepts in mathematics and the knowledge gained will greatly influence him at the next level of education. In this independent curriculum, teachers must be more creative in developing learning materials, especially in lower classes. Mathematics learning in grade 1 SDN Bendogerit 2 shows results that have not reached the predetermined completeness criteria, namely the value of 70 or 70% classical completeness. Learning outcomes in grade 1 obtained results that have not reached completeness, namely from 17 students who achieved completeness as many as 7 students or 41%. Based on these results, the teacher conducted a qualitative descriptive research action research, with a learning method that was attempted to increase students' understanding of concepts by using appropriate learning methods. The learning method used is Realistic Mathematics, which is a learning method that links children's real life experiences with mathematical ideas into important classroom learning so that learning is meaningful.